2016
DOI: 10.4314/majohe.v7i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Framework for the Study of Employee Commitment

Abstract: This paper is a conceptual discussion of the construct of employee commitment identifying its antecedents in an organisational context. While the paper is of general interest to human resource management (HRM), it arose as part of a study on the commitment of academic staff in universities in Uganda. The paper suggests a framework for studying employee commitment, and proposes 21 hypotheses for future research basing on a review of recent literature. Each hypothesis suggests an antecedent. The antecedents are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 85 publications
2
10
0
3
Order By: Relevance
“…Therefore, training is an organised strategy for learning and development to enhance individual employees, team, and organisational effectiveness (Fletcher et al 2018). Training enhances leadership development, learning new work skills, socialisation of new employees to the culture of an organisation, understanding job responsibilities, and business ethics (Mugizi et al, 2015). Studies (Aybas & Acar, 2017;Baker, 2017;Memon et al, 2020;Sawasdee et al, 2020;Semwal & Dhyani, 2017;Siddiqui & us-Sahar, 2019;Sivapragasam & Raya, 2017) reported that training relates to employee engagement.…”
Section: Training and Teacher Engagementmentioning
confidence: 99%
“…Therefore, training is an organised strategy for learning and development to enhance individual employees, team, and organisational effectiveness (Fletcher et al 2018). Training enhances leadership development, learning new work skills, socialisation of new employees to the culture of an organisation, understanding job responsibilities, and business ethics (Mugizi et al, 2015). Studies (Aybas & Acar, 2017;Baker, 2017;Memon et al, 2020;Sawasdee et al, 2020;Semwal & Dhyani, 2017;Siddiqui & us-Sahar, 2019;Sivapragasam & Raya, 2017) reported that training relates to employee engagement.…”
Section: Training and Teacher Engagementmentioning
confidence: 99%
“…Alat ukur yang digunakan untuk mengukur pre-test dan post-test adalah Measure of Employee Commitment buatan Allen dan Meyer's [8]. Pada umumnya alat ukur ini memang dibuat untuk menilai komitmen karyawan di konteks organisasi [6].…”
Section: Metodologiunclassified
“…Pada umumnya alat ukur ini memang dibuat untuk menilai komitmen karyawan di konteks organisasi [6]. Namun seiring dengan berjalannya waktu, alat ukur ini telah diuji validitas dan reliabilitasnya dalam konteks pendidikan [8], serta digunakan untuk mengukur consumer community commitment [9]. Bunyi butir disesuaikan dengan konteks partisipan sebagai anggota komunitas.…”
Section: Metodologiunclassified
“…Employee commitment reflects the involvement and psychological attachment that an employee has towards an organization and work which is assigned to him or her. According to Mugizi, Bakkabulindi, and Bisaso (2015), employee commitment is a bond between the employee and the organization-where the employee wants to continue serving the organization and to help it achieve its objectives. Meyer, Stanley and Parfyonova (2012), described commitment as an internal psychological force that makes an individual stick to a course of action that is of relevance to a particular goal.…”
Section: Employees Performancementioning
confidence: 99%